Bioinspired multifunctional injectable hydrogel for hemostasis and infected wound management. (15th April 2023) - Fang, Wen; Yang, Ling; Chen, Yihao; Hu, Qiaoling
Abstract: Routine wound management faces significant challenges including rebleeding and bacterial infection that affect millions of people each year. However, conventional wound dressings (e.g., gauze, bandage) are limited to simply cover the injured surfaces and rarely show special functionality to promote the wound recovery. Currently, injectable hydrogels have been widely designed as multifunctional wound dressings to manage the hemostatic and wound healing process. Nevertheless, the integration of multiple functions through simple composition and easy construction is still difficult and hardly achieved. Herein, we reported a bioinspired multifunctional injectable hydrogel (CQCS@gel) consisted of only two components, catechol-functionalized quaternized chitosan (CQCS) and dibenzaldehyde-terminated poly(ethylene glycol) (DB-PEG2000 ). The building blocks endowed CQCS@gel with tissue-adhesive, antibacterial, antioxidant, self-healing and pH-responsive properties. Based on the in vivo hemostatic study, quick hemostasis for acute tissue injuries such as liver and carotid wounds was realized owing to the rapid gelation rate and strong tissue-adhesiveness of CQCS@gel. Moreover, CQCS@gel remarkably boosted the chronic recovery process of MRSA-infected cutaneous wounds by promoting collagen deposition, hair follicles regeneration and angiogenesis. Overall, this multifunctional injectable hydrogel shows potentials as a universal wound dressing in clinical applications, enabling both hemostasis and infected wound management. Statement of significance: This is the first report showing the multifunctional injectable hydrogel (CQCS@gel) consisted of catechol-functionalized quaternized chitosan and dibenzaldehyde-terminated poly(ethylene glycol). The incorporation of quaternary ammonium groups imparted the CQCS@gel with outstanding contact-active bacterial killing efficiency and the catechol moieties enhanced its tissue adhesive and antioxidant properties. Moreover, the reversible imine crosslinks endowed the CQCS@gel with self-healing and pH-responsive drug release capabilities. These multiple functions were integrated into a single injectable hydrogel system with easy availability and low cost. In vitro and in vivo results showed that the newly designed hydrogel was biocompatible, realized successful sealing hemostasis under multiple bleeding scenarios and enabled accelerated healing of infected skin wounds. Graphical abstract: Image, graphical abstract